We're dragging our heels but there is enough evidence to support making facemasks mandatory - Caffrey, Louise (Irish Independent, 2020)
During the Covid-19 pandemic, the Health Information and Quality Authority (Hiqa) has been advising the Clinical Expert Advisory Group in supporting the National Public Health Emergency Team. Most recently, Hiqa reviewed the evidence on the use of face coverings to prevent people from transmitting the Covid-19 virus. As a result, current policy is to only recommend the public wear face coverings rather than making them compulsory on, for example, public transport, in shops and in services.
PUBLISHED
Irish Independent
Keywords: Evidence Based Policy; PUBLIC HEALTH